First record of Eutrombicula tinami (Oudemans, 1910) (Trombidiformes: Trombiculidae) parasitizing a cat in Brazil - Cousandier, G. (2021)
Chigger mites are ectoparasites of terrestrial tetrapods and can cause dermatitis in the host, known as trombiculiasis. In Brazil, there are 73 species of chiggers; however, cats never have recorded as a host in this country. Here, we report the first record of chiggers parasitizing a domestic cat in Brazil; and a new locality for Eutrombicula tinami (Oudemans 1910) in the Rio Grande do Sul state, Brazil.